School Management Effectiveness: The Analysis Of Organizational Culture, Leadership Style, Work Environment, And Satisfaction - Virgana, Virgana; Suradika, Agus (International Journal of Educational Management and Innovation, 2022)
In school management, several variables support the effectiveness of the principal’s performance. The study analyzed the effects of exogenous to endogenous, directly or indirectly, and work satisfaction as a variable intervening. This study was a quantitative survey with a sample size are 360 state high school teachers. Data analysis uses path analysis. With the help of Smart partial least squares software, data that meets the criteria r > 0.70 will be used in the research. The results showed that organizational culture, leadership style, and work environment significantly affect work satisfaction. The organizational culture, leadership style, and work satisfaction directly affect teachers’ performance. The organizational culture, leadership style, and work environment significantly indirectly affect work satisfaction on teachers’ performance. In organizational culture, instruments have involved working together in bearing burdens culture as the potential of the community for empowerment again; it is a novelty of this research. The results of research that require follow-up is how to improve the principal leadership style with the hope that micro-school management is more effective and macro enhancing the quality of education in Indonesia